Europe and the post-Yugoslav space - Radeljić, Branislav (Routledge, 2016)
Charting the path from intervention to integration Europe and the Post-Yugoslav Space examines the role of Europeanization on the development of the countries of the former Yugoslavia. Slovenia, Croatia, Macedonia, Montenegro, Serbia, Bosnia and Herzegovina and Kosovo may have a shared history but their experiences, views and attitudes to European integration vary dramatically. Opinion within each state is often equally as keenly divided as to the benefits of active membership. The debate within each country and their comparative differences in approach provide fascinating case studies on the importance and relevance of the EU and the effectiveness of Europeanization.